We want them, but we don't want them: the case of undocumented college students in Colorado: an interpretation of policy narratives - Castro, Liliana N., author; Harbour, Clifford P., advisor; Banning, James H., committee member; Flahive, Douglas, committee member; Quick, Donald, committee member (Colorado State University. Libraries, 2011)
This dissertation describes a research project that examined and interpreted the text of Colorado House Bill 1023 (2006) and the narratives embedded in this policy text. The research context was framed by current debates at the national and state levels on the issue of postsecondary education benefits for undocumented students. Analysis of the data led to the illumination of the rationalization for denying in-state tuition benefits to undocumented graduates from public high-schools in Colorado. This rationalization was found to be based on selected ideological beliefs that were then identified and interpreted. The study employed a qualitative research design. The method of inquiry was grounded in a constructivist-interpretive methodology. The methods of analysis and interpretation were thematic analysis, hermeneutic interpretation, and narrative policy analysis. The data consisted of Colorado policy texts concerning immigration and membership issues, related federal legislation, and state statutes from Texas and California. The data were first analyzed using thematic networks analysis and then hermeneutic interpretation. Narrative policy analysis was subsequently employed to synthesize the themes that emerged in the thematic analysis and hermeneutic interpretation. A dominant policy narrative and counter policy narrative were generated, and from these a metanarrative evolved. The thematic analysis yielded an internal or legalistic interpretation of the verification regulations of lawful presence requirement set forth in Colorado HB 06S-1023. The hermeneutic interpretation revealed that this Colorado policy was framed according to the principle of self-sufficiency for immigrant admission and notions of restrictive membership for resident aliens. The interpretive analysis also showed that the interaction of negative constructions of undocumented immigrants with structures of social dominance led to a narrative of exclusion and objectification of these resident aliens. The narrative policy analysis related Colorado HB 06S-1023 to a dominant policy narrative that reinforced the legal grounds for the delegitimization and social exclusion of undocumented immigrants. A metanarrative derived from the comparison of these narratives and was interpreted as the contrast between we want them, but we don't want them to explain how official government texts of the state of Colorado rationalized the issue of undocumented immigrants' rights and the state's responsibilities in this regard. The interpretation of the data contributed perspectives that advance the understanding of the social issue regarding the restriction on public benefits for undocumented immigrants currently residing in American communities. Specifically, this interpretation provided insights on the case of undocumented students in Colorado who, as a result of current state legislation, are denied access to in-state tuition benefits. The study also contributed another approach to meaning-creation processes and understanding the meaning of a policy text. Recommendations for further research on this topic and related themes were identified.
Keywords: higher education; undocumented college students; policy